2018
DOI: 10.1126/science.aau7224
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying reputation and success in art

Abstract: In areas of human activity where performance is difficult to quantify in an objective fashion, reputation and networks of influence play a key role in determining access to resources and rewards. To understand the role of these factors, we reconstructed the exhibition history of half a million artists, mapping out the coexhibition network that captures the movement of art between institutions. Centrality within this network captured institutional prestige, allowing us to explore the career trajectory of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(149 citation statements)
references
References 24 publications
3
145
0
1
Order By: Relevance
“…In both visual art and across artistic fields, research has shown that advantageous associations can be professional, such as membership within an artistic movement (Crane 1987;White and White 1965;for example, see pp. 6-17), mentorship between an established and novice artist (Craig and Dubois 2010), or attending a prominent academy or school (Madoff 2009); however, informal associations also prove beneficial, ranging from friendship circles and social milieus (Currid 2007; gateway to prestigious, successful careers (Braden 2009;Fraiberger et al 2018), exhibition association is particularly powerful, denoting critical comparability and a historical relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In both visual art and across artistic fields, research has shown that advantageous associations can be professional, such as membership within an artistic movement (Crane 1987;White and White 1965;for example, see pp. 6-17), mentorship between an established and novice artist (Craig and Dubois 2010), or attending a prominent academy or school (Madoff 2009); however, informal associations also prove beneficial, ranging from friendship circles and social milieus (Currid 2007; gateway to prestigious, successful careers (Braden 2009;Fraiberger et al 2018), exhibition association is particularly powerful, denoting critical comparability and a historical relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Even if someone tried to directly assess the creativity of a Product, of the Process behind it, or of the Person, he needs to pass through the lens of human perception (and thus the Press perspective) to be really understood (Colton, 2008), making the Press perspective the most ubiquitous. On the other hand, the Press perspective is not enough to give an indication of creativity, since commercial success or reach of a Product is influenced by a variety of factors that go beyond creativity, or even just its Value (Fraiberger et al, 2018).…”
Section: Pressmentioning
confidence: 99%
“…A third perspective, the institutionalist approach, stresses the role of institutional intermediaries and the exchanges of information that determine the formation of reputation: the existence of specific market institutions such as contests (Rao, 1994), the undertaking of high levels of value-creating market actions directed to increase a firm's visibility (Rindova et al, 2007), or the association with high reputation actors (Stuart et al, 1999) have been considered within this framework. In a recent empirical application to the arts, Fraiberger et al (2018) emphasize connections to reputed institutions in the creation of symbolic value. Their research quantifies reputation of artists using the prestige of the museums and galleries where their work has been exhibited.…”
Section: Reputation and Brand Equitymentioning
confidence: 99%